Hubungan Karakteristik, Cara Persalinan, dan Derajat Keparahan COVID-19 dengan Derajat Afiksia Neonatus di RSUD Tugurejo Jawa Tengah Tahun 2020-2022 - Rafi Aryanto Arif; Sri Rejeki; Devita Diatri (PT. Hasba Edukasi Mandiri, 2026)
Background: Pregnant women are a group that is vulnerable to infection and can experience more severe symptoms due to physiological changes in the body's immunity during pregnancy. The severity of COVID-19 is divided into 3, namely: mild symptoms, moderate symptoms and severe symptoms. In pregnant women who experience hypoxia, theoretically, it can have an impact on the condition of the fetus and neonate which can affect the neonate's APGAR score. The APGAR score test is a method for assessing the health condition of neonates in the first and fifth minutes after the baby is born and consists of 5 criteria, namely: activity, pulse, grimace, appearance, and respiration with a maximum score of 10. A low APGAR score should be watched out for because it can be associated with an increased risk of neonatal death. Conditions such as intrauterine hypoxia, fetal inflammatory response syndrome, and premature birth are feared to occur in mothers with COVID-19 infection, so this needs to be investigated further to use the APGAR score to assess fetal outcomes from mothers with COVID-19 infection. It is hoped that the APGAR score will be useful for determining the next treatment steps that will be carried out by medical personnel. Method: This research method is quantitative observational analytic with a cross-sectional design. The research subjects were COVID-19-positive mothers who gave birth at Tugurejo Regional Hospital, Central Java in 2020-2022. The research tool used is a medical record. The sampling technique used was total sampling. The statistical tests used are the Kruskal-Wallis Test and Spearman rank. Result: The total sample that met the inclusion criteria was 102 patients. The results of the comparison test of the mean APGAR scores in the mild, moderate, and severe severity groups using the non-parametric Kruskal-Wallis Test obtained a p-value of 0.000, and the Spearman rank correlation test obtained a p-value of 0.000 with a 1st Minute APGAR correlation coefficient of + 0.551 which means the two variables have a strong correlation and the 5th Minute APGAR has a correlation direction of +0.452, which means the two variables have a sufficient correlation and have a positive correlation direction. Conclusion: The worse the mother's symptoms of COVID-19 are, the worse the neonatal APGAR score will be in patients giving birth at Tugurejo Regional Hospital, Central Java.